An In-Depth Study on the Emergence of Eighteen Early Buddhist Schools - Medhācitto, Tri Saputra (STAB Kertarajasa, 2024)
This qualitative study utilizes a comprehensive library research approach, focusing on both primary and secondary sources to explore the chronological background on the emergence of early Buddhist schools. Primary sources include the canonical, chronicles and other Pāli literatures. While secondary sources include previous research articles and books written by scholars. This research discovered that the Buddhist councils held by the leading disciples after the demise of the Buddha played a significant role in the division of Buddhist order and the emergence of Buddhist schools. Buddhist councils were mainly convened to discuss and resolve controversial issues that arose within the order. Schism in the Buddhist order emerged as result of disagreements in regard to philosophical teaching and the practice of vinaya. Disagreements among the monks in the second Buddhist council led to the division of Buddhist order into two primary schools known as Theravāda and Mahāsaṅgika. From these two primary Buddhist schools, gradually eighteen Buddhist schools emerged, with twelve schools deriving from Theravāda and six from Mahāsaṅgika. This research deals with an in-depth study on the emergence of eighteen early Buddhist schools).